2022
DOI: 10.1371/journal.pone.0273092
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting hydrodynamic regimes of submerged pinnacle and emergent coral reefs

Abstract: Hydrodynamics on coral reefs vary with depth, reef morphology and seascape position. Differences in hydrodynamic regimes strongly influence the structure and function of coral reef ecosystems. Submerged coral reefs on steep-sided, conical bathymetric features like seamounts experience enhanced water circulation as a result of interactions between currents and the abrupt physical structure. There may also be similar interactions between smaller pinnacles and regional water currents in offshore locations (crests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…We suggest that these mechanisms are like the enhanced biophysical‐coupling and energetic focusing found to occur on seamounts (White et al 2007; Lavelle and Mohn 2010). The pinnacles in our study have been shown to possess distinct hydrodynamic regimes, characterized by markedly higher current speeds compared to the nearshore and offshore emergent reefs (Galbraith et al 2022). Through localized hydrodynamics generated at submerged and steep‐side reef morphologies, we propose that the habitat quality is enhanced for reef fishes on pinnacle coral reefs, despite small overall area, greater depths and relative isolation in offshore positions.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We suggest that these mechanisms are like the enhanced biophysical‐coupling and energetic focusing found to occur on seamounts (White et al 2007; Lavelle and Mohn 2010). The pinnacles in our study have been shown to possess distinct hydrodynamic regimes, characterized by markedly higher current speeds compared to the nearshore and offshore emergent reefs (Galbraith et al 2022). Through localized hydrodynamics generated at submerged and steep‐side reef morphologies, we propose that the habitat quality is enhanced for reef fishes on pinnacle coral reefs, despite small overall area, greater depths and relative isolation in offshore positions.…”
Section: Discussionmentioning
confidence: 64%
“…Temperature variables were somewhat important for fish species richness and abundance but were some of the least influential variables for fish biomass. Although average annual temperatures on the pinnacles are slightly cooler than emergent reefs in Kimbe Bay (Galbraith et al 2022), the magnitude of this difference is small and seasonal patterns are remarkably low here (Srinivasan and Jones 2006). Our previous investigation of hydrodynamic regimes and thermal profiles on the pinnacles in Kimbe Bay hints at potential thermoregulatory processes at these sites but this has not been empirically shown.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation